The Effect of Using Joint Audit on the Timely Issuance of Auditor’s Report in Banks Accepted in the Iraqi Stock Market - AL-SHADEEDI, SADEQ JAAFAR HAMEED; dastjerdi, Mohsen rahimi; KHAFAJI, NATIQ JABBAR SALIM; Saedi , Rahman (Journal of Ecohumanism, 2025)
The Iraqi stock market is of great importance as one of the leading financial markets in the region, and banks operating in this market play a key role in providing financial resources and economic development. Joint auditing is an effective method to increase audit quality and public confidence in financial reports, which has also been recommended to a number of Iraqi banks. This research uses quantitative and qualitative research methods to collect and analyze the data. First, to collect data and information, the library method has been used, and inthe data section of the research, referring to the financial statements, explanatory notes, and the monthly journal of the stock exchange has been used. Then, these data are analyzed using statistical methods to investigate the impact of joint audit on the timely issuance of auditor reports. The results of this study show that the use of joint audit can significantly improve the timely issuance of auditor’s report in banks listed in the Iraqi stock market.